Impact of the COVID-19 pandemic on dental and medical education in Bangladesh: a pilot study and the implications (Bangladesh Journal of Medical Science, 2022)
Objective: Lockdown and other measures, including the closure of universities, introduced by Governments across countries in response to the COVID-19 pandemic have appreciably impacted on the education of dental and medical students across countries. Key challenges included the need to rapidly move to e-learning as well as instigate new approaches to practicals for health science students. This involves lecturers and students necessarily needing to rapidly adapt to e-learning and other approaches. There have also been affordability issues among students to regularly access the Internet, and purchase the necessary equipment, particularly among those from low- and middle-income countries such as Bangladesh. Consequently, there is an urgent need to assess current challenges among senior level physicians and educators in Bangladesh regarding the education of dental and medical students arising from the current pandemic, and how these are being addressed, to provide future direction. This is particularly important in Bangladesh with high rates of both infectious and non-infectious diseases.Materials and Methods: Pragmatic investigation involving a purposely developed questionnaire based on previous studies and the experience of the co-authors. The questionnaire was distributed to 15 senior-level educators with the findings analysed by themes.Results: Key issues included little experience with e-learning at the start of the pandemic among both staff and students, poor internet access and cost of internet bundles. In addition, fear and anxieties among both students and staff. The colleges responded by instigating teaching classes for educators on e-learning and providing adequate personal protective equipment for staff and students during teaching and practical sessions. These formed the basis of future recommendations. Other recommendations included increased flexibility among staff and students.Conclusion: The pandemic posed appreciable challenges to both staff and students attending dental and medical colleges in Bangladesh. Some of the key issues are starting to be addressed.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 444-454